Comparison of clinical efficacy between proximal femoral locking plate and cannulated compression screws for femoral neck fracture - Zhou, Xianglong; Wei, Dongxuan; Xiao, Jiheng; Xia, Tianyi; Zhou, Haoran; Xiang, Jianhui; Fang, Hanhong; Song, Hui; Xiong, Liming (Frontiers in Surgery, 2025)
ObjectiveThe objective of this study is to investigate the clinical efficacy of proximal femoral locking plates in comparison to cannulated compression screws for the treatment of femoral neck fractures.MethodsA retrospective analysis of clinical data from 50 patients with femoral neck fractures treated at the Department of Orthopaedics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology from September 2018 to June 2023. Patients were divided into 25 in the PFLP group and 25 in the CCS group. A comparison was made between the two groups in terms of the following variables: basic characteristics, perioperative information, and information during follow-up visits.ResultsThe basic characteristics of the two groups were found to exhibit no statistically significant differences (P > 0.05). The PFLP group had significantly longer surgical times and greater Intraoperative hemorrhage loss compared to the CCS group (P < 0.05). The statistical analysis revealed that there were no significant differences in intraoperative fluoroscopy times and Garden index between the two groups (P > 0.05). The PFLP group exhibited a markedly superior fracture healing time, femoral neck shortening, and Harris hip scores in comparison to the CCS group (P < 0.05). The postoperative complication rates were 12% in the PFLP group and 20% in the CCS group, with no statistically significant difference (P > 0.05).ConclusionThe results of this retrospective study suggest that the PFLP group demonstrated superior outcomes compared to the CCS group in several key areas, including fracture healing time, preservation of femoral neck length, recovery of hip function, and incidence of postoperative complications.